A contribuição da associação entre genealogia acadêmica e bibliometria para a avaliação de Programas de Pós-Graduação - Moura, Vanessa Paula Alves de (Universidade Federal de São Carlos, 2020)
The measurement of scientific production is an object of studies much explored in Information Science, through Bibliometrics, which allows to evaluate the performance of researchers and the impacts of their productions, and have the results bibliometric indicators, which are useful to understand reality and act in different situations. Technological evolution allowed the improvement of Bibliometrics and has also benefited other studies, such as Academic Genealogy, which, more recently, has been used to analyze the performance of researchers and the impacts of their actions on Science, through the relationship between supervisor and its oriented. One of the most recent studies in Brazil on Academic Genealogy, is based on the Lattes Platform and the extraction of these data is done by software called AGLattes, developed by researchers in the field of Computer Science. Although the data obtained are rich and valuable, there is little research that uses them for the purpose of complementing bibliometric indicators. Therefore, this study aims to investigate whether the application of Academic Genealogy and bibliometric analysis together can bring relevant information about the contribution of a Postgraduate Program in the training of researchers and in the production of knowledge. For the execution of the research, the Postgraduate Program in Materials Engineering of the Federal University of São Carlos - PPGCEM/UFSCar - was chosen, which originated in the first course of Materials Engineering in Brazil. The analysis was made from all teachers which are in the program since its foundation, a total of 58 teachers. As these professors work in other programs, a procedure was developed that made it possible to reach only researchers who have their origin in PPGCEM/UFSCar, eliminating the contamination of data from other programs and allowing to obtain information from 993 direct and 1205 indirect descendants. To extract the scientific production of the Lattes Curriculum of these descendants, the software Lattes Machine was used and later data mining and bibliometric analyzes were performed using the VantagePoint software. The results are illustrated by bibliometric indicators built from the association of Academic Genealogy with Bibliometrics, which provide valuable information about the program, the human resources trained and all their descendants, such as where they work, how they are distributed around the world and in Brazil, the training area, in addition to information about its scientific productions that can be used in the elaboration of strategies, in the self-assessment of graduate programs aiming at guaranteeing the quality and obtaining resources from development agencies, in this case the CAPES. The study also contributes to verify the historical and current importance of PPGCEM/UFSCar and its researchers for the program area and for Science.
The contribution of the association between academic genealogy and bibliometry for the evaluation of Graduate Programs
Keywords: Bibliometria; Indicadores bibliométricos; Genealogia acadêmica; Plataforma Lattes; Engenharia de Materiais; Bibliometrics; Bibliometric indicators; Academic genealogy; Lattes Platform; Materials Engineering; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::METODOS QUANTITATIVOS. BIBLIOMETRIA